Manajemen Pelatihan Dai Cilik dalam Mengembangkan Keterampilan Dakwah Siswa Sekolah Dasar IT Alwashliyah Kelambir Lima Medan - Fathiha Zahra Damanik; Muktarruddin Muktarruddin (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to analyze the management of young preacher (dai cilik) training in developing students’ preaching skills at SD IT Al-Washliyah Kelambir Lima Medan using a management function approach (*planning, organizing, actuating, and controlling*). This study employed a descriptive qualitative method, with data collected through in-depth interviews, participant observation, and documentation. The research informants consisted of the principal and teachers responsible for the young preacher training program. The collected data were analyzed systematically to describe the implementation of management functions in the young preacher training activities and their contribution to the development of students’ preaching skills. The results showed that planning was carried out through the development of a practice-based preaching curriculum, organizing was implemented through task allocation and regular scheduling, implementation focused on *public speaking* practice, sermon material preparation, and moral development, while evaluation was conducted periodically through student performance assessments. The implementation of this systematic training management contributed to the improvement of students’ preaching skills in cognitive, affective, and psychomotor aspects. These findings indicate that management functions applied in a structured manner play a strategic role in supporting the development of students’ preaching competencies at the elementary school level. Furthermore, continuous training provides opportunities for students to enhance their self-confidence, communication skills, and readiness to effectively deliver Islamic preaching messages